Integrating Content Expertise and Methodological Expertise in Team‐Based Settings to Address Complex Societal Issues—A Systems Perspective on Challenges. (4th July 2018) - Hogan, Michael; Broome, Benjamin; Harney, Owen; Noone, Chris; Dromgool‐Regan, Cushla; Hall, Tony; Hayden, Sandra; O'Higgins, Siobhán; Khoo, Su‐Ming; Moroney, Mike; O'Reilly, John; Pilch, Monika; et al.
Abstract : Systems‐based approaches to societal problem‐solving entail a capacity to synthesise our knowledge and skills such that we can resolve shared problems. However, the increasing range of knowledge specialisms, scientific and engineering methods, and skill profiles at the population‐level challenges solidarity. It is also difficult to identify unifying goals and establish sustainable educational infrastructures that support transdisciplinary teamwork. Drawing upon the collective intelligence of a multidisciplinary group, this paper highlights challenges to integrating content expertise and methodological expertise in team‐based efforts to address complex social issues. Challenges identified include the following: stakeholder participation, heterogeneity and conflict, supporting effective group dynamics, defining goals, planning and resourcing, resistance and fears amongst group members, and the absence of effective teamwork methodologies. A systems model developed by the group helped to clarify interdependencies between challenges. We conclude by highlighting the need to develop societal infrastructures supporting our capacity for teamwork into the future. © 2018 John Wiley & Sons, Ltd.